2012
DOI: 10.3113/fai.2012.0767
|View full text |Cite
|
Sign up to set email alerts
|

Operative Technique of Two Parallel Compression Screws and Autologous Bone Graft for Ankle Arthrodesis after Failed Total Ankle Replacement

Abstract: The results from this small series of patients suggest that arthrodesis following failed total ankle replacement with two parallel screws and bone graft may be an effective technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…11 The method of fixation has also been pointed out as one of the key factors to achieve a successful arthrodesis. Different methods of fixation have been used in the literature: combination of screws, 4,6,8,[13][14][15]26 blade plate, 2,4,6,8,9,20,26 nail, || external fixation, [15][16][17] and Kirschner wires. 8 The use of a retrograde intramedullary nail has been suggested by several authors to be the method of choice in fusion after failed total ankle replacements, especially in cases with large bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…11 The method of fixation has also been pointed out as one of the key factors to achieve a successful arthrodesis. Different methods of fixation have been used in the literature: combination of screws, 4,6,8,[13][14][15]26 blade plate, 2,4,6,8,9,20,26 nail, || external fixation, [15][16][17] and Kirschner wires. 8 The use of a retrograde intramedullary nail has been suggested by several authors to be the method of choice in fusion after failed total ankle replacements, especially in cases with large bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral approach and described method of screw insertion from the talus have also been applied in patients undergoing arthrodesis after failed ankle arthroplasty [11]. Bohne et al [5], who modified Mann's technique, achieved arthrodesis in 39 out of 41 feet operated on in the period of 14 weeks .…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaver model, Somberg et al found no difference in biomechanical stability between three Acutrak HCSs and three traditional screws [10]. Jehan and O’Hill presented a technique for parallel compression screw fixation enhanced with autologous bone graft, even in difficult cases after failed ankle arthroplasty [18]. Kennedy et al confirmed that a simple two-screw technique supported with biological and mechanical principles can achieve excellent fusion rates [15].…”
Section: Discussionmentioning
confidence: 99%
“…AAA has gained popularity among orthopedic surgeons over the last two decades [5, 6]. Fixation methods to maintain proper foot alignment long enough to achieve solid bone union, without the need for early hardware removal, is still a major concern [7-18]. Here, we present the results of AAA in 24 patients (25 ankles) with fixation by two parallel 7.3-mm mediolateral headless compression screws (HCSs) in different clinical indications.…”
Section: Introductionmentioning
confidence: 99%